Study of the Structural Properties of NiCl2:Al2O3 Thin Film Prepared by Chemical Thermal Spraying Technique (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: The structural properties of films are studied by several techniques, and X-ray diffraction (XRD) is one of the most reliable methods that were adopted in this research, so will explain it in some detail, in addition to assays (SEM ) that give information on surface morphology. Materials and Methods: The thermochemical spraying technique was used to prepare the thin films. Results: The results showed that increasing the temperature led to a decrease in the average particle size, in contrast to the doping process. Conclusion: The reason for the decrease in particle size is due to the increase in the Full Width at Half Maximum (FWHM) in addition to an increase in the crystallization of the thin films, and also the membrane becomes more regular and crystalline defects decrease and increase.